Modernité, Postmodernité Et Impérialisme Occidental - Maurice Gning (European Scientific Journal, ESJ, 2018)
The objective of this study is to underscore the close link between modernity and postmodernity, two ideologies that are, quite often, opposed. Based on history, geopolitics, interculturality and the views of thoerists and critics of these thoughts, mainly those of Lyotard, Derrida, Foucautlt and the marxists, this paper attempts to demonstrate that the opposition between the two ideologies is only formal. They have the same purpose, namely to fulfil an imperialist task. If modernity is the thought of colonialist Europe at the time of the industrial revolution, postmodernity is that of neocolonialist America in the age of globalization. Both are carriers of universal chaos.